Preman Pensiun dan Kuasa Agama: Semiotika Visual Komunikasi Religius dalam Episode “Kembali Ke Fitri” - Dudi Rustandi; Anna Noviana (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2022)
The Preman Pensiun cinema in the episode Return to Fitri has vital elements of the pull of religion so that humans return to Him. The purpose of this study is to interpret cultural signs visually. Using a critical paradigm with a visual semiotic method that is both structural and poststructural, the researcher uses a post-semiotic approach rooted in postmodernism to interpret the image that the author refers to from the Sinema Preman Pensiun episode of Return to Fitri. The study's results, from the perspective of structural visual semiotics, show that the power of religion is clearly depicted in the scenes played by Muslihat and Ujang figures. However, in the post-semiotic perspective, the pull of religion is a method of capitalism to influence or grip the minds of the audience so that they are interested in being part of the film (the audience). This research is expected to impact researches on communication semiotics that continue to develop and on da'wah communication in general, which the authors define as religious communication in the context of a critical paradigm.